Development of Quizizz-based Assessment Instruments for Grade IV Elementary Students - Wahidah, Miftahul; Hadikusuma Ramadan, Zaka (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2025)
The present study sets out to design an assessment tool using Quizizz to evaluate understanding of the values and meaning of Pancasila among fourth-grade elementary students. The study applied the ADDIE development framework, which consists of five key steps: Analysis, Design, Development, Implementation, and Evaluation. According to assessments by two language experts, the instrument was deemed highly valid and dependable. The first expert assigned an average score of 81%, while the second gave 90%, resulting in an overall average of 85%, placing the tool in the